A unicorn named Sparkle - Young, Amy (2016)
"A picture book about a little girl who desperately wants a beautiful unicorn as a pet, but winds up with a less than desirable one instead"--
Illustrations were rendered using watercolor and ink
Marantz copy has the original dust jacket
Ages 3-6
Marantz copy has the original paper covered boards with illustrations on front and back covers. Illustrated endpapers
Keywords: Unicorns -- Juvenile fiction; Goats -- Juvenile fiction; Pets -- Juvenile fiction; Children$1 (Bs bookss; Fiction; Picture books; Paper case bindings; Illustrated case bindings; Book jackets; Illustrated endpapers